Hybrid cryptosystems for the protection of FANET network nodes: approaches to use - Hrushak, S.S.; Huzii, M.M.; Bezvershenko, E.I. (Problems of Informatization and Management, 2024)
The article presents the results of research into the possibility of using hybrid cryptosystems to protect FANET sensor network nodes. A model of a hybrid cryptosystem for data encryption, generation of a shared secret key is proposed, and an authentication algorithm in the FANET network based on the TLS protocol and symmetric/asymmetric encryption methods is developed. AES-GCM, ECDSA algorithms were tested for encryption and decryption operations, time characteristics of operations were measured, the number of CPU cycles and energy consumption were determined. As a result of the conducted research, the expediency of using hybrid cryptosystems by nodes of FANET networks is substantiated, provided that certain requirements for hardware, software and energy resources are met.